PENTINGNYA METODE EDUKASI DIDAKTIF TENTANG KESEHATAN MATA OLEH TENAGA REFRAKSI OPTISI BAGI SISWA/I SD - Wulan Ayuningtias; Murni Marlina Simarmata; Zakaria Efendi (Jurnal Mata Optik, 2022)
This study aims to determine the effectiveness of the didactic education method by refractionist optician health workers for grade 6 students at Ciomas 01 Elementary School. The subjects of this study were 10 people, 6th-grade students, at Ciomas 01 Elementary School. The research method used was qualitative by collecting data. Through the interview process, filling out questionnaires, and observation. From the results of the study, it can be concluded that the teacher's role is very dominant in the process of providing material on eye health so that students can better understand the material about eye health and the provision of material on eye health using the didactic method is considered effective to be applied to 6th-grade students at Ciomas 01 Elementary School.